2017
DOI: 10.1523/jneurosci.3845-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptors Differentially Control Binge Alcohol Drinking-Mediated Synaptic Plasticity of the Core Nucleus Accumbens Direct and Indirect Pathways

Abstract: Binge alcohol drinking, a behavior characterized by rapid repeated alcohol intake, is most prevalent in young adults and is a risk factor for excessive alcohol consumption and alcohol dependence. Although the alteration of synaptic plasticity is thought to contribute to this behavior, there is currently little evidence that this is the case. We used drinking in the dark (DID) as a model of binge alcohol drinking to assess its effects on spike timing-dependent plasticity (STDP) in medium spiny neurons (MSNs) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 67 publications
4
33
0
Order By: Relevance
“…Neighbors et al concluded that time-speci c calendar events [29] and event-speci c drinking [30] were associated with increased levels of bingeing. However, neurobiological changes may occur with repetitive binge-drinking conditions [31,32], and may increase cravings [33]. Ghiţă et al reported a variability of the levels of alcohol craving in relation to the day of the week, and drinking during weekends in Spain (Friday, Saturday, or Sunday) was associated with greater craving levels in patients with alcohol use disorder [17].…”
Section: Associations Between Dependence Signs and Increased Drinkingmentioning
confidence: 99%
“…Neighbors et al concluded that time-speci c calendar events [29] and event-speci c drinking [30] were associated with increased levels of bingeing. However, neurobiological changes may occur with repetitive binge-drinking conditions [31,32], and may increase cravings [33]. Ghiţă et al reported a variability of the levels of alcohol craving in relation to the day of the week, and drinking during weekends in Spain (Friday, Saturday, or Sunday) was associated with greater craving levels in patients with alcohol use disorder [17].…”
Section: Associations Between Dependence Signs and Increased Drinkingmentioning
confidence: 99%
“…The NAc exhibits substantial synaptic alterations after voluntary drinking and passive alcohol vapor exposure. In NAc MSNs of naïve male mice, postsynaptic depolarization paired with low frequency presynaptic stimulation typically leads to long‐term depression (LTD) of excitatory transmission in D1 MSNs and long‐term potentiation (LTP) (Ji et al., ) or no change in excitatory transmission in D2 MSNs (Renteria et al., ). Voluntary binge drinking shifts this plasticity to LTP in D1 MSNs and prevents LTP induction in D2 MSNs (Ji et al., ).…”
Section: Sex Differences In Nacmentioning
confidence: 99%
“…In NAc MSNs of naïve male mice, postsynaptic depolarization paired with low frequency presynaptic stimulation typically leads to long‐term depression (LTD) of excitatory transmission in D1 MSNs and long‐term potentiation (LTP) (Ji et al., ) or no change in excitatory transmission in D2 MSNs (Renteria et al., ). Voluntary binge drinking shifts this plasticity to LTP in D1 MSNs and prevents LTP induction in D2 MSNs (Ji et al., ). In fact, even after the first drink of alcohol, enhancements in excitatory synaptic transmission in D1 cells are detected (Beckley et al., ).…”
Section: Sex Differences In Nacmentioning
confidence: 99%
See 2 more Smart Citations